WOMEN'S CONTRIBUTION AS PROFESSIONALS AND WOMEN AS ENTREPRENEURS TO THE WOMEN'S HUMAN DEVELOPMENT INDEX (IPM) IN JAVA ISLAND - Qurrota Ayun; Imam Mukhlis (International Journal Labs, 2022)
Indonesia faces the problem of a low HDI for women, this problem is caused by the low contribution of women in the country's economy. In fact, the HDI for women is still not evenly distributed in all districts/cities throughout Indonesia. In fact, the issue of HDI for women is not only a problem of inequality in Java and outside Java, the problem of inequality also occurs in regencies/cities on the island of Java. This study intends to analyze the partial and simultaneous contribution of women entrepreneurs and women's professional workers to HDI women in Java. The research data uses secondary data in the form of women's HDI data documents, data on women entrepreneurs and data on women professional workers that have been calculated by Central Bureau of Statistics, then the data is analyzed using multiple linear regression and cross-variable tests. The results of the study found that there was a simultaneous positive influence on the contribution of women entrepreneurs and professional women workers to the HDI of women, partially only the variable of professional women workers had a significant positive effect on the HDI of women. While the variable of women as entrepreneurs has no significant positive effect on women's HDI in Java.